Size structure, the pattern of growth and the average length at first captured by fish Madidihang (Thunnus albacares) in the waters of Bitung - Franky Adrian Darondo; Sugianto sugianto Halim; Wudianto Wudianto Wudianto; Meuthia Aula Jabbar (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2020)
Bitung City is the center of fisheries industries in North Sulawesi. Fisheries production in Bitung Oceanic Fishing Port showed an increasing trend until the first semester of 2019. Yellowfin tuna is the dominant catches that landed at the port. Along with the increasing fishing efforts but lack of information regarding capture size, research to support its sustainable management need to be carried out. This study aims to determine the average size structure from four type fishing gears used by fishermen, the growth pattern, and the length at first captured (Lc). Fish were sampled randomly from landed catches at Bitung fishing port. The samples were taken from August 2019 to October 2019 with the total number of 3,900 fish samples. The results from the purse seine showed that Lc of yellowfin 47.32 cm FL. Comparing to the length at first maturity (Lm) from the previous research result of 94 cm Fl, it can be concluded that the first catches were of young fish (juvenile). If this continues to happen without being balanced by a management effort, it will lead to overfishing that endangers the sustainability of yellowfin fish resources.Keywords: Purse seine, yellowfin, length, growth pattern, Bitung City.